Optimal performance of silicon nanowire solar cells under low sunlight concentration and their integration as bottom cells in III–V multijunction systems - Yu Jeco-Espaldon, Bernice Mae; Jevasuwan, Wipakorn; Okada, Yoshitaka; Fukata, Naoki (Frontiers in Nanotechnology, 2024)
Nanostructured silicon solar cells are designed to minimize costs through reduced material usage while enhancing power conversion efficiency via superior light trapping and shorter charge separation distances compared to traditional planar cells. This study identifies the optimal conditions for nanoimprinted silicon nanowire (SiNW) solar cells to achieve maximum efficiency under low sunlight concentration and evaluates their performance as bottom cells in III-V multijunction solar cell systems. The findings indicate that the SiNW solar cell reaches its peak performance at a concentration factor of 7.5 suns and a temperature of 40°C or lower. Specifically, the absolute conversion efficiency under these conditions is 1.05% higher than that under unconcentrated light. When compared to a planar silicon solar cell under identical conditions, the SiNW solar cell exhibits a 3.75% increase in conversion efficiency. Additionally, the SiNW single junction solar cell, when integrated in series with a commercial lattice-matched InGaP/GaAs dual junction solar cell, was tested under unconcentrated sunlight, specifically at one-sun, global air mass 1.5 condition, to assess its viability in one-sun multijunction solar cell applications. The results suggest that a III-V upper subcell with a smaller active area than the SiNW is optimal for current production, which is favorable to cost reduction of the device. This hybrid configuration is particularly advantageous for terrestrial applications, such as electric vehicles, which demand lightweight, high-performance multijunction solar cell devices. Although the weight reduction of the characterized SiNW solar cell with a full silicon substrate compared to its planar solar cell counterpart is 1.8%, recommendations to improve this reduction to as much as 64.5% are discussed to conclude this paper.